Karakterisasi Alat Filtrasi Air Portable Berdasarkan Variasi Jumlah Absorber Karbon Aktif Limbah Tongkol Jagung - Amrullah, Shafwan; Yanti, Sahri; As'urin, B. (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Sumbawa Regency is an area with soil water content containing lime. There was even lime blockage in the pipe holes used. So this research aims to create a portable filtration device that is cheap and efficient. The aim of this research is to characterize a portable water filtration device with an innovative absorber from corncob waste. The way this research works is the process of carbonizing corn cob waste and then activating it using 0.5 M NaOH for 24 hours. The absorber is then filled into a portable filter with dimensions of 50 cm in length and 4 inches in diameter. Filtration is carried out by flowing the collected well water into the water reservoir through a filter. Tests are carried out on water that has not been passed through a filter. After that, characterization was also carried out on the water that had passed through the filter. This characterization consists of Total Dispended Solid (TDS), Temperature, pH, Ca levels, and turbidity. The TDS value obtained decreases with the increasing number of absorbers used, namely from 203, 163, to 123 ppm. In addition, the temperature of the test water has almost no change. The resulting results were temperatures of 32, 33, and 32oC. The resulting pH value shows a decrease with an increase in the number of absorbers used, namely from 8.3; 7.7; 7.3. For turbidity, there was a decrease in the turbidity rate with an increase in the number of absorbers used, namely from 0.29 NTU to 0.3 NTU, and 0.28 NTU. In addition, CaCO3 levels decreased with an increase in the number of absorbers used, namely from 330 mg/l, 290 mg/l, and 240 mg/l. This value has met the threshold set by PMK No. 32 of 2017.